Modified response evaluation criteria in solid tumors is superior to response evaluation criteria in solid tumors for assessment of responses to sorafenib in patients with advanced hepatocellular carcinoma. (December 2015) - Takada, Juichi; Hidaka, Hisashi; Nakazawa, Takahide; Kondo, Masaaki; Numata, Kazushi; Tanaka, Katsuaki; Matsunaga, Kotaro; Okuse, Chiaki; Kobayashi, Satoshi; Morimoto, Manabu; Ohkawa, Shinichi; Koizumi, Wasaburo
Abstract Background Modified response evaluation criteria in solid tumors (mRECIST) and RECIST are used to assess the effect of treatment with targeted agents for hepatocellular carcinoma (HCC). The aim of this study was to determine which set of criteria is superior in patients with advanced HCC treated with sorafenib. Methods A multicenter retrospective study to assess the tumor response and patient prognosis of 191 patients with HCC who had been treated with sorafenib from May 2009 through December 2011. We analyzed tumor responses as shown by contrast-enhanced computed tomography scan images according to RECIST 1.1 and mRECIST and compared the findings. Results The median duration of follow-up was 9.7 months and median overall survival was 10.8 months. Twenty-five patients (13.1 %) were assessed as responders by mRECIST and 15 (7.8 %) by RECIST 1.1. There was a significant difference in overall survival (OS) between responders and non-responders according to mRECIST (P = 0.0117), but no significant difference in OS between responders and non-responders according to RECIST 1.1 (P = 0.0722). Sixteen patients (8.4 %) had no measurable enhanced target lesions that could be assessed as required by mRECIST; however, these patients could be assessed by RECIST 1.1. According to RECIST 1.1, eight of them had stable disease (SD) and eight had progressive disease (PD). There was a significant difference in OS between these SD and PD patients (P = 0.0312). Conclusions Patients treated with sorafenib for HCC should be evaluated by mRECIST; RECIST 1.1 is preferable only for assessment of patients with lesions that are non-measurable according to mRESIST.